2011
DOI: 10.1016/j.toxlet.2011.05.1037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of manganese oxide nanoparticles and manganese sulfate with regard to oxidative stress, uptake and apoptosis in alveolar epithelial cells

Abstract: Due to their physicochemical characteristics, metal oxide nanoparticles (NPs) interact differently with cells compared to larger particles or soluble metals. Oxidative stress and cellular metal uptake were quantified in rat type II alveolar epithelial cells in culture exposed to three different NPs: manganese(II,III) oxide nanoparticles (Mn(3)O(4)-NPs), the soluble manganese sulfate (Mn-salt) at corresponding equivalent doses, titanium dioxide (TiO(2)-NPs) and cerium dioxide nanoparticles (CeO(2)-NPs). In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 50 publications
(55 reference statements)
4
51
0
4
Order By: Relevance
“…The production of reactive oxygen species (ROS) by BFO HNPs in cell cultures was assessed using two fluorescence assays: dihydroethidium (DHE) and carboxydichlorodihydrofluorescein diacetate (DCFH-DA). 16,17 We could detect a dose-dependent increase of ROS, more pronounced in A549 cells than in HTB-182 ( Fig. 2C1 and C2), which remains however low compared to that induced by other metal-based NPs.…”
mentioning
confidence: 80%
“…The production of reactive oxygen species (ROS) by BFO HNPs in cell cultures was assessed using two fluorescence assays: dihydroethidium (DHE) and carboxydichlorodihydrofluorescein diacetate (DCFH-DA). 16,17 We could detect a dose-dependent increase of ROS, more pronounced in A549 cells than in HTB-182 ( Fig. 2C1 and C2), which remains however low compared to that induced by other metal-based NPs.…”
mentioning
confidence: 80%
“…The composition of nanoparticle-containing medium solutions was characterized by inductively coupled plasma optical emission spectroscopy (ICP OES, Horiba Ultra 2). A detailed description of the nanoparticle preparation is given elsewhere 11 . More detailed information is enclosed in the supporting information.…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated that the effects in MAC are trolox-sensitive, but only can speculate that ROS-induced modified activity of several protein kinases regulating inflammatory pathways might cause the measured changes in MCP-1 expression 41 . It has certainly to be mentioned that the influence of antioxidants already present in cells and epithelial lining fluid (gluthatione, ascrobate, uric acid) might play an important role in the modification of the inflammatory response 11 . In addition, MAC and AEC were observed under in vitro conditions using rat cell lines, which do not accurately mimic the conditions in a living organism.…”
Section: Ros-mediated Decrease In Viability Of Macrophages Only Margmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] Within cells, ceria nanoparticles tend to agglomerate. [48,49] Cytotoxic effects of nanoceria can be greatly reduced by preventing the internalization of the NPs into cells, for example by encapsulating them into a hydrogel. Weaver and Stabler [50] demonstrated that their alginate hydrogel prevented the phagocytosis of dextran-coated nanoceria and thus reduced their cytotoxicity, while preserving the antioxidative and protective properties of these particles.…”
Section: Toxicity Of Nanoceriamentioning
confidence: 99%